SEKILAS WAYANG PANJI (GEDHOG) DAN FILSAFAT JAWA - S., Suyanto (Institut Seni Indonesia Surakarta, 2016)
Javanese wayang consists of several kinds for example Wayang Purwa, Wayang Gedhog, WayangMadya, and Wayang Wasana. According to Serat Centini, Wayang Gedhog appeared in fifteenthcentury created by Sunan Ratu Tunggul in the era of Demak. Problems of the article include whatkind of values contained in Wayang Gedhog performance is? This article is supposed to describethe values of life contained in Wayang Gedhog. The values are analyzed by theory of philosophyadapted to the new paradigm in the development of philosophy today. The finding tells that thejourney of Panji Asmarabangun represents a spiritual act that leads to the deepest spiritual level.The obstacles passed by Panji shows the symbol of evil lust.Keywords: Wayang Gedhog, Panji, symbol, Philosophy, value.